The draft genome of the microscopic Nemertoderma westbladi sheds light on the evolution of Acoelomorpha genomes - Abalde, Samuel; Tellgren-Roth, Christian; Heintz, Julia; Vinnere Pettersson, Olga; Jondelius, Ulf (Frontiers in Genetics, 2023)
Background: Xenacoelomorpha is a marine clade of microscopic worms that is an important model system for understanding the evolution of key bilaterian novelties, such as the excretory system. Nevertheless, Xenacoelomorpha genomics has been restricted to the few species that either can be cultured in the lab or are centimetres long. Thus far, no genomes are available for Nemertodermatida, one of the group’s main clades and whose origin has been dated more than 400 million years ago. Methods: DNA was extracted from a single specimen and sequenced with HiFi following the Pacbio Ultra-low Input DNA Protocol. After genome assembly, decontamination, and annotation, the genome quality was benchmarked using two acoel genomes and one Illumina genome as reference. The gene content of three cnidarians, three acoelomorphs, four deuterostomes, and eight protostomes was clustered in orthogroups to make inferences of gene content evolution. Finally, we focused on the genes related to the ultrafiltration excretory system to compare patterns of presence/absence and gene architecture among these clades. Results: We present the first nemertodermatid genome sequenced from a single specimen of Nemertoderma westbladi. Although genome contiguity remains challenging (N50: 60 kb), it is very complete (BUSCO: 80.2%, Metazoa; 88.6%, Eukaryota) and the quality of the annotation allows fine-detail analyses of genome evolution. Acoelomorph genomes seem to be relatively conserved in terms of the percentage of repeats, number of genes, number of exons per gene and intron size. In addition, a high fraction of genes present in both protostomes and deuterostomes are absent in Acoelomorpha. Interestingly, we show that all genes related to the excretory system are present in Xenacoelomorpha except Osr, a key element in the development of these organs and whose acquisition seems to be interconnected with the origin of the specialised excretory system. Conclusions: Overall, these analyses highlight the potential of the Ultra-Low Input DNA protocol and HiFi to generate high-quality genomes from single animals, even for relatively large genomes, making it a feasible option for sequencing challenging taxa, which will be an exciting resource for comparative genomics analyses.